1999
DOI: 10.1016/s0014-5793(99)01480-5
|View full text |Cite
|
Sign up to set email alerts
|

Starvation induces tau hyperphosphorylation in mouse brain: implications for Alzheimer's disease

Abstract: Hyperphosphorylated tau is the major component of paired helical filaments in neurofibrillary tangles found in Alzheimer's disease brains, and tau hyperphosphorylation is thought to be a critical event in the pathogenesis of this disease. The objective of this study was to reproduce tau hyperphosphorylation in an animal model by inducing hypoglycemia. Food deprivation of mice for 1 to 3 days progressively enhanced tau hyperphosphorylation in the hippocampus, to a lesser extent in the cerebral cortex, but the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 37 publications
5
83
1
1
Order By: Relevance
“…1-4). As described qualitatively (16), tau undergoes phosphorylation and dephosphorylation, illustrated here by phosphorylation-dependent anti-tau antibody AT8 (Fig. 1, A1 and B1).…”
Section: Starvation Up-regulates Activating Phosphorylation Of Mapk Asupporting
confidence: 57%
See 2 more Smart Citations
“…1-4). As described qualitatively (16), tau undergoes phosphorylation and dephosphorylation, illustrated here by phosphorylation-dependent anti-tau antibody AT8 (Fig. 1, A1 and B1).…”
Section: Starvation Up-regulates Activating Phosphorylation Of Mapk Asupporting
confidence: 57%
“…Reduced glucose metabolism is associated with certain regions of the brain of probable and preclinical AD subjects (19,20), and is considered by some as aggravating, if not causative in the development of AD (21). These data, combined with the observations that starvation induces tau hyperphosphorylation at many PHF-tau epitopes, and with a regional selectivity analogous to that in AD, suggest that a common mechanism might be mobilized in starvation and AD for tau hyperphosphorylation (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrating that modulations of glucose or insulin levels alter tau antigenicity in neuronal cultures support this hypothesis (Cheng and Mattson, 1992;Hong and Lee, 1997;Lesort et al, 1999). We also reported that starvation, which decreases the amount of circulating glucose and insulin and lowers glucose utilization (Newsholme, 1976;Cherel et al, 1988), induces AD-like tau hyperphosphorylation in mice (Yanagisawa et al, 1999;Planel et al, 2001).…”
Section: Introductionmentioning
confidence: 71%
“…For example, in mice hyperphosphorylation of tau protein, a significant step in AD etiology, may be induced by starvation. 11 On the other hand, brain-derived neurotrophic factor, a factor that plays a controlling role in neuroprotection, is increased in the hippocampus and cerebral cortex in rats on a dietary restriction. 12 Given these differing findings, it is of interest to study whether weight change influences the cognitive performance of elderly citizens.…”
Section: Introductionmentioning
confidence: 99%